The Colonial origins of Philippine institutions - Cruz, Prince Christian R.
This paper attempts to trace the origins of Philippine institutions, more specifically, institutions that do not adequately protect rights and do not provide effective constraints on the actions of the elite. Extending a model developed by Acemoglu, Johnson and Robinson [2001], this paper provides a framework for analyzing the incentive structure faced by individuals that lead them to demand, create and preserve certain institutions. An explicit rational-choice framework is used to derive the demand for institutions of Spanish settlers. Following the basic dictum that institutions evolve to minimize uncertainty, this paper argues that Spaniards in the Philippines developed extractive institutions in order to minimize the uncertainty brought by the high level of mortality and the low level of wealth in the Philippines, and the unstable nature of property rights in Spain and its colonies.